Pengaruh Pendidikan dan Pelatihan Terhadap Kinerja Karyawan Universitas - M Mursidi (Jurnal Teknik Industri, 2009)
Result of analysis show the carrying out of training and education very good with rate score 227,8. rate of employee performance very good with rate score 226. Result of regression analysis show traiming and aducation influenced to performance employee with coefisien regression value 0,911. Coefisien determination value 0,644, show that training and aducation influence to employee performance 64.4 %. Resercher suggestion, Muhammadiyah University of Malang should maintain and increase the employee performances.